Protective role of Nrf2 in zinc oxide nanoparticles-induced lung inflammation in female mice and sexual dimorphism in susceptibility. (1st November 2022) - Sehsah, Radwa; Wu, Wenting; Ichihara, Sahoko; Hashimoto, Naozumi; Zong, Cai; Yamazaki, Kyoka; Sato, Harue; Itoh, Ken; Yamamoto, Masayuki; Elsayed, Ahmed Ali; El-Bestar, Soheir; Kamel, Emily; et al.
Abstract: Background: Zinc oxide nanoparticles (ZnO-NPs) are currently employed in various products such as rubber, paint, and cosmetics. Our group reported recently that Nrf2 protein provides protection against pulmonary inflammation induced by ZnO-NPs in male mice. The current study investigated the effect of Nrf2 deletion on the lung inflammatory response in female mice exposed to ZnO-NPs. Methods: An equal number of female Nrf2 -/- mice and female Nrf2 +/+ mice (24 each) were allocated into three equal groups, and each was exposed to ZnO-NPs at either 0, 10 or 30 µg ZnO-NPs/mouse through pharyngeal aspiration. Bronchoalveolar lavage fluid (BALF) and lungs were examined 14 days later to determine the number of inflammatory cells, the protein level, and for scoring inflammation histopathologically. The mRNA levels of Nrf2 -dependent antioxidant enzymes and proinflammatory cytokine in lung tissue were also measured. Results: Exposure to ZnO-NPs increased all types of BALF cells and lung inflammation scores in both of female Nrf2-null ( Nrf2 -/- ) and wild-type ( Nrf2 +/+ ) mice, and Nrf2 deletion enhanced ZnO-NPs-induced increase in the number of eosinophils in BALF. Exposure to ZnO-NPs dose-dependently increased the level of oxidized glutathione (GSSG), and mRNA levels of proinflammatory cytokines/chemokines; KC, MIP-2, IL-6, IL-1β and MCP-1 only in wild-type mice. Nrf2 deletion decreased total glutathione levels and basal mRNA levels of SOD1 and NQO1, and increased the basal mRNA level of above proinflammatory cytokines/chemokines. Nrf2 deletion enhanced ZnO-NPs-induced downregulation of GcL c, GR and TGF-β and upregulation of HO-1 and TNF-α. Taken together with our previous results in male mice, our results showed a lower susceptibility of females to lung tissue inflammation, relative to males, irrespective of Nrf2 deletion, and that enhancement of ZnO-NPs-induced upregulation of HO-1 and TNF-α and downregulation of GcL c, GR and TGF-β by deletion of Nrf2 is specific to female mice. Conclusion: We conclude that Nrf2 provides protection in female mice against increase in BALF eosinophils, probably through down-regulation of proinflammatory cytokines/chemokines and upregulation of oxidative stress-related genes. The study also suggests lower susceptibility to lung tissue inflammation in female mice relative to their male counterparts and the synergistic effects of Nrf2 and exposure to ZnO-NPs on mRNA expression of GcL c, GR, HO-1, TGF-β or TNF-α in female mice . Highlights: Nrf2 protects female mice against increase in BALF eosinophils. Female mice are less susceptible to lung tissue inflammation than male mice. Nrf2 and ZnO-NP synergistically regulate expression of GcLc, GR, HO-1, TGF-β or TNFα.